Solid waste technology and management : Volume 2 - Christensen, Thomas H. (Chichester, England : Wiley, 2011)
A comprehensive introductory text covering a wide range of topics in a vast subject area. * Environmental protection is a 'hot topic' and this is a critical time in the development of environmental awareness.
Preface xi List of Contributors xiii VOLUME 1 1 INTRODUCTION 1.1 Introduction toWaste Management 3 Thomas H. Christensen 1.2 Introduction toWaste Engineering 17 Thomas H. Christensen 1.3 Introduction toWaste Economics 29 Hanna Merrild and Thomas H. Christensen 1.4 Introduction toWaste Legislation and Regulation 52 Peter Pagh and Henrik Wejdling 2 WASTE GENERATION AND CHARACTERIZATION 2.1 Waste Characterization: Approaches and Methods 63 Anders Lagerkvist, Holger Ecke and Thomas H. Christensen 2.2 Residential Waste 85 Thomas H. Christensen, Thilde Fruergaard and Yasushi Matsufuji 2.3 Commercial and InstitutionalWaste 97 Thomas H. Christensen and Thilde Fruergaard 2.4 IndustrialWaste 100 Thomas H. Christensen 2.5 Construction and DemolitionWaste 104 Thomas H. Christensen and Lizzi Andersen 3 LCA OF WASTE MANAGEMENT SYSTEMS 3.1 LCA inWaste Management: Introduction to Principle and Method 113 Michael Hauschild and Morton A. Barlaz 3.2 Application of LCA inWaste Management 137 Anna Bjorklund, Goran Finnveden and Liselott Roth 3.3 LCA Modeling of Waste Management Scenarios 161 Thomas H. Christensen, Federico Simion, Davide Tonini and Jacob Moller 4 WASTE MINIMIZATION 4.1 Waste Prevention and Minimization: Concepts, Strategies and Means 183 Stefan Salhofer, Nicole Unger and Bernd Bilitewski 4.2 Waste Prevention and Minimization: Cases 193 Stefan Salhofer and Nicole Unger 5 MATERIAL RECYCLING 5.1 Recycling of Paper and Cardboard 203 Thomas H. Christensen and Anders Damgaard 5.2 Recycling of Glass 211 Thomas H. Christensen and Anders Damgaard 5.3 Recycling of Plastic 220 Thomas H. Christensen and Thilde Fruergaard 5.4 Recycling of Metals 234 Anders Damgaard and Thomas H. Christensen 5.5 Recycling of Construction and DemolitionWaste 243 Thomas H. Christensen and Harpa Birgisdottir 6 COLLECTION 6.1 Waste Collection: Equipment and Vehicles 253 Per Nilsson 6.2 Waste Collection: Systems and Organization 277 Per Nilsson and Thomas H. Christensen 6.3 Source Segregation and Collection of Source-Segregated Waste 296 Thomas H. Christensen and Yasushi Matsufuji 6.4 Waste Transfer Stations 311 Thomas H. Christensen 7 MECHANICAL TREATMENT 7.1 Mechanical Treatment: Unit Processes 321 Bernd Bilitewski 7.2 Mechanical Treatment: Material Recovery Facilities 349 Thomas H. Christensen and Bernd Bilitewski 8 THERMAL TREATMENT 8.1 Incineration: Process and Technology 365 Tore Hulgaard and Jurgen Vehlow 8.2 Incineration: Flue Gas Cleaning and Emissions 393 Jurgen Vehlow and Soren Dalager 8.3 Incineration: Mass Balances 421 Soren Dalager and Dieter O. Reimann 8.4 Incineration: Solid Residues 430 Ole Hjelmar, Annette Johnson and Rob Comans 8.5 Incineration: Utilization of Residue in Construction 463 Maria Arm, T. Taylor Eighmy and Thomas H. Christensen 8.6 Incineration: Co-combustion 476 Helmut Rechberger 8.7 Incineration: RDF and SRF - Solid Fuels fromWaste 486 Susanne Rotter 8.8 Pyrolysis and Gasification 502 Thomas Astrup and Bernd Bilitewski VOLUME 2 9 BIOLOGICAL TREATMENT 9.1 Composting: Process 515 Edward Stentiford and Marco de Bertoldi 9.2 Composting: Technology 533 Uta Krogmann, Ina Korner and Luis F. Diaz 9.3 Composting: Mass Balances and Product Quality 569 Alessio Boldrin, Thomas H. Christensen, Ina Korner and Uta Krogmann 9.4 Anaerobic Digestion: Process 583 Irini Angelidaki and Damien John Batstone 9.5 Anaerobic Digestion: Technology 601 Jes la Cour Jansen 9.6 Anaerobic Digestion: Mass Balances and Products 618 Jacob Moller, Thomas H. Christensen and Jes la Cour Jansen 9.7 Mechanical Biological Treatment 628 Bernd Bilitewski, Christiane Oros and Thomas H. Christensen 9.8 Emerging Biological Technologies: Biofuels and Biochemicals 639 Dimitar Karakashev and Irini Angelidaki 9.9 Use of Compost in Horticulture and Landscaping 651 Morten Carlsbaek 9.10 Utilization of Biologically Treated Organic Waste on Land 665 Peter E. Holm, Lars Stoumann Jensen and Michael J. McLaughlin 10 LANDFILLING 10.1 Landfilling: Concepts and Challenges 685 Thomas H. Christensen, Heijo Scharff and Ole Hjelmar 10.2 Landfilling: Environmental Issues 695 Thomas H. Christensen, Simone Manfredi and Peter Kjeldsen 10.3 Landfilling: Hydrology 709 Peter Kjeldsen and Richard Beaven 10.4 Landfilling: Geotechnology 734 R. Kerry Rowe and Jamie F. VanGulck 10.5 Landfilling: Mineral Waste Landfills 755 Ole Hjelmar and Hans A. van der Sloot 10.6 Landfilling: Reactor Landfills 772 Thomas H. Christensen, Simone Manfredi and Keith Knox 10.7 Landfilling: MBP Waste Landfills 788 Rainer Stegmann 10.8 Landfilling: Bottom Lining and Leachate Collection 800 Thomas H. Christensen, Simone Manfredi, Peter Kjeldsen and Robert B. Wallace 10.9 Landfill Top Covers 830 Charlotte Scheutz and Peter Kjeldsen 10.10 Landfilling: Gas Production, Extraction and Utilization 841 Hans Willumsen and Morton A. Barlaz 10.11 Landfilling: Leachate Treatment 858 Hans-Jurgen Ehrig and Howard Robinson 10.12 Landfilling: Planning, Siting and Design 898 Roberto Raga, Raffaello Cossu and Anders Lagerkvist 10.13 Landfilling: Operation and Monitoring 914 Nicole D. Berge, Eyad S. Batarseh and Debra R. Reinhart 10.14 Landfill Closure, Aftercare and Final Use 932 Heijo Scharff 11 SPECIAL AND HAZARDOUS WASTE 11.1 Healthcare RiskWaste 951 Ole Vennicke Christiansen and Peder Bisbjerg 11.2 Waste Electrical and Electronic Equipment 960 Marianne Bigum and Thomas H Christensen 11.3 Preservative Treated Wood 971 Ina Korner, Jenna Jambeck, Hans Leithoff and Volker Lenz 11.4 Hazardous Waste 982 Joan Maj Nielsen and Jorn Lauridsen 11.5 Other Special Waste 991 Line Brogaard and Thomas H. Christensen Index 1001
Includes bibliographical references and index.
Keywords: REFUSE AND REFUSE DISPOSAL